Conversor CA-CC monofásico bidirecional com estágio integrado e isolação em alta frequência aplicável a carregamento on-board de veículos elétricos - Barbosa, Samanta Gadelha (2020)
This work proposes the study and development of a bidirectional single-phase AC-DC converter with single stage and high frequency isolation, feasible to electrical vehicles. The proposed converter is based on the interleaving concept and switching cells coupling to obtain a prototype with high power density. Those characteristics make the topology an excellent solution for applications with high power level where weight and volume must be limited. Thus, within this work is developed a theoretical analysis for the proposed structure, validated through simulation on the software PSIM and experimental results using a 1kW prototype. Closed loop tests are presented verifying the dynamic performance and the controller’s stabilization capabilities. Being this topology bidirectional, assays on both rectifier and inverter modes are discussed, proving the capability of operation in both modes with 90% efficiency. In rectifier mode the FP was 0.996 with current THD of 2.8% and in inverter mode, connecting a DC source to the power grid, the FP was 0.995 with current THD of 7.6%. The obtained results were satisfactory, validating the theoretical analysis and, consequently, the topology efficacy in applications with high power density, however some improvements like magnetics integration and zero voltage switching showed up to be necessary in order to elevate its efficiency, making the structure more adequate for applications on electrical vehicles with on-board chargers.